Quadrivalent Ann Arbor strain live-attenuated influenza vaccine. (November 2012) - Toback, Seth L; Levin, Myron J; Block, Stan L; Belshe, Robert B; Ambrose, Christopher S; Falloon, Judith
Influenza B is responsible for significant morbidity in children and adults worldwide. For more than 25 years, two antigenically distinct lineages of influenza B viruses, B/Yamagata and B/Victoria, have cocirculated globally. Current influenza vaccine formulations are trivalent and contain two influenza subtype A strains (A/H1N1 and A/H3N2) but only one B strain. In a half of recent influenza seasons, the predominant circulating influenza B lineage was different from that contained in trivalent influenza vaccines. A quadrivalent live-attenuated influenza vaccine (Q/LAIV) that contains two B strains, one from each lineage, has been developed to help provide broad protection against influenza B. Q/LAIV was recently approved for use in the USA in eligible individuals 2–49 years of age. This review summarizes clinical trial data in support of Q/LAIV.